Coupling a tree growth model with storm damage modeling – Conceptual approach and results of scenario simulations. (July 2015) - Albrecht, Axel Tim; Fortin, Mathieu; Kohnle, Ulrich; Ningre, François
Abstract: The purpose of this study was to develop, test and evaluate a software prototype capable of modeling forest growth in consideration of winter storm disturbance and to simulate storm damage in forests under different forest management regimes. The results of a test application showed that simulated storm damage was more strongly influenced by the input data (e.g. tree species and tree height) than by the different forest management regimes. However, early, intense thinnings as well as reducing target diameters by 10% led to reduced storm damage, with decreases as large as 50% of the damage in certain forest stands. The coupled modeling framework was able to simulate interactions between forest growth, storm damage and forest management regimes. Further testing of the prototype appears necessary to investigate a wider range of tree species, soil and site conditions. Also, the use of computational system resources needs improvement. Highlights: We establish and evaluate a coupled forest growth and storm damage modeling system. The impact of forest management on storm damage risk can be simulated. Measures to stabilize forest ecosystems against storm disturbance were identified. Heavy thinnings and a 10% reduction of target diameters proved effective. Storm damage in coniferous forests could be lowered up to 50% by adapted management.